PROFIL TINGKAT MOTIVASI SISWA TUNARUNGU DALAM BELAJAR PENDIDIKAN JASMANI ADAPTIF - Solihin, Akhmad Olih (STKIP Pasundan, 2016)
This study aims to determine the profile of the level of motivation of students in extraordinary schools citeureup in following the Physical Education learning. This research uses quantitative descriptive methods. The population is all students with hearing impairment at SLB Citeureup with the sample used are 15 students with hearing impairment with a sampling technique using perposive sampling that is sampling as desired. The data collection technique used was a questionnaire. Data analysis technique used is Descriptive statistics with Percentages. Based on research results show that the high and low frequency of student learning by 16.9%, the high and low length of student learning by 10.4%, the high and low need to know and learn an object by 16.7%, and environmental factors by 16, 7% shows that these factors are included in the less category, as well as the high and low factors of supporting attention in increasing student motivation by 39.3% which are categorized as sufficient. The results of this study can be concluded that the level of motivation of deaf students in learning Physical Education has the highest price of 39.3%. This shows that the learning motivation of physical education for deaf students in SLB Citeureup is in the category of Enough so that it needs to be improved again.